(untitled) (Journal of Parents and Teachers, 2026)
The collection of anecdotes and memories from children about their grandparents reflects how they perceive their presence, affection, and teachings. These anecdotes reflect the emotional importance of grandparents. Even after their death, we can see how grandparents influence the formation of values, habits, and the happiest memories of children.